2014
DOI: 10.3390/antibiotics3040527
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Chemokine CXCL10 for Dermal and Oral Microorganisms

Abstract: CXCL10 (IP-10) is a small 10 kDa chemokine with antimicrobial activity. It is induced by IFN-γ, chemoattracts mononuclear cells, and promotes adhesion of T cells. Recently, we detected CXCL10 on the surface of the skin and in the oral cavity. In the current study, we used broth microdilution and radial diffusion assays to show that CXCL10 inhibits the growth of Escherichia coli, Staphylococcus aureus, Corynebacterium jeikeium, Corynebacterium striatum, and Candida albicans HMV4C, but not Corynebacterium bovis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…CXCL10 and CXCL8 are inflammatory chemokines. CXCL10 is induced by IFN-γ, which can enhance innate antimicrobial defense, chemoattracts mononuclear cells and promotes adhesion of T cells 8 18 19 . CXCL8 can enhance microglial matrix metalloproteases production, leading to breakdown of the blood-brain barrier and invasion of inflammatory cells, thereby enhancing the inflammatory cascade that contributes to nerve damage 20 .…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 and CXCL8 are inflammatory chemokines. CXCL10 is induced by IFN-γ, which can enhance innate antimicrobial defense, chemoattracts mononuclear cells and promotes adhesion of T cells 8 18 19 . CXCL8 can enhance microglial matrix metalloproteases production, leading to breakdown of the blood-brain barrier and invasion of inflammatory cells, thereby enhancing the inflammatory cascade that contributes to nerve damage 20 .…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 is a small 10-kD protein that has an unstructured N-terminal region, three anti-parallel β-strands, and an amphipathic C-terminal α-helix ( Cole et al, 2001 ; Frederick and Clayman, 2001 ; Booth et al, 2002 ; Swaminathan et al, 2003 ). Notably, the positively charged, amphipathic α-helix has been generally thought to be responsible for the observed antimicrobial activity of the molecule because of the overall charge and structural similarity to defensins or cationic antimicrobial peptides ( Brogden, 2005 ; Yeaman and Yount, 2007 ; Holdren et al, 2014 ). Recently, we observed that a C-terminal truncated CXCL10 (designated CTTC) retained antimicrobial activity (albeit, with somewhat less potency) against B. anthracis Sterne strain (hereby designated parent strain), but not against B. anthracis Δ ftsX ( Margulieux et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The CXCL10 in gingival crevicular fluid was detected at picogram levels , while the concentrations of CXCL10 that showed antimicrobial activity in vitro were present at microgram levels ; thus, it is not clear whether antimicrobial chemokines can indicate the antimicrobial activity in actual gingival tissue. Moreover, CXCL10 did not have antimicrobial activity against bacteria that commonly inhabit the oral cavity . However, antimicrobial chemokines from GFs were strongly induced by the relatively less‐pathogenic bacteria, and this showed that the concentrations of antimicrobial chemokines can be increased by invasion of bacteria into the gingival tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Structural analyses of chemokines have revealed that their structure, which is defined by disulfide bonds, anti‐parallel β‐strands and a C‐terminal α‐helix, is similar to that of the defensins ; consequently, their antimicrobial activity is thought to result from their structural similarity to the defensins . Several investigators discovered that the chemokines from chemokine (C‐X‐C motif) ligand (CXCL)9, CXCL10, CXCL11, CXCL6, CXCL14, chemokine (C‐C motif) ligand (CCL)17, CCL20, CCL22 and CCL28 have antimicrobial properties . The expression of CXCL10, CXCL11 and CCL20 has been reported in human GFs ; however, the regulation of their expression by oral bacteria has rarely been reported.…”
mentioning
confidence: 99%